Repeatability and reliability of GABA measurements with magnetic resonance spectroscopy in healthy young adults. Issue 5 (20th November 2020) - Duda, Jessica M.; Moser, Amelia D.; Zuo, Chun S.; Du, Fei; Chen, Xi; Perlo, Sarah; Richards, Christine E.; Nascimento, Nara; Ironside, Maria; Crowley, David J.; Holsen, Laura M.; Misra, Madhusmita; et al.
Abstract : Purpose: Gamma‐aminobutyric acid (GABA) abnormalities have been implicated in a range of neuropsychiatric disorders. Despite substantial interest in probing GABA in vivo, human imaging studies relying on magnetic resonance spectroscopy (MRS) have generally been hindered by technical challenges, including GABA's relatively low concentration and spectral overlap with other metabolites. Although past studies have shown moderate‐to‐strong test‐retest repeatability and reliability of GABA within certain brain regions, many of these studies have been limited by small sample sizes. Methods: GABA+ (macromolecular‐contaminated) test‐retest reliability and repeatability were assessed via a Meshcher‐Garwood point resolved spectroscopy (MEGA‐PRESS) MRS sequence in the rostral anterior cingulate cortex (rACC; n = 21) and dorsolateral prefrontal cortex (dlPFC; n = 20) in healthy young adults. Data were collected on a 3T scanner (Siemens Prisma, Siemens Healthcare, Erlangen, Germany) and GABA+ results were reported in reference to both total creatine (GABA+/tCr) and water (GABA+/water). Results: Results showed strong test‐retest repeatability (mean GABA+/tCr coefficient of variation [CV] = 4.6%; mean GABA+/water CV = 4.0%) and reliability (GABA+/tCr intraclass correlation coefficient [ICC] = 0.77; GABA+/water ICC = 0.87) in the dlPFC. The rACC showed acceptable (but comparatively lower) repeatability (mean GABA+/tCr CV = 8.0%; mean GABA+/water CV = 7.5%), yet low‐moderate reliability (GABA+/tCr ICC = 0.40; GABA+/water ICC = 0.44). Conclusion: The present study found excellent GABA+ MRS repeatability and reliability in the dlPFC. The rACC showed inferior results, possibly because of a combination of shimming impedance and measurement error. These data suggest that MEGA‐PRESS can be utilized to reliably distinguish participants based on dlPFC GABA+ levels, whereas the mixed results in the rACC merit further investigation.